Performance of 3D diamond detectors in small field dosimetry: The impact of pixel size. (October 2022) - Kanxheri, Keida; Talamonti, Cinzia; Sciortino, Silvio; Lagomarsino, Stefano; Ionica, Maria; Caprai, Mirco; Moscatelli, Francesco; Servoli, Leonello
Abstract: Purpose: Small photon beams used in radiotherapy techniques have inherent characteristics of charge particle disequilibrium and high-dose gradient making accurate dosimetry for such fields very challenging. By means of a 3D manufacturing technique, it is possible to create arrays of pixels with a very small sensitive volume for radiotherapy dosimetry. We investigate the impact of 3D pixels size on absorbed dose sensitivity, linearity of response with dose rate, reproducibility and beam profile measurements. Methods: Diamond detectors with different pixel sizes have been produced in the 3DOSE experiment framework. To investigate the pixels size impact, they were tested using an Elekta Synergy LINAC. Dose rate dependence, absorbed dose sensitivity, reproducibility and beam profile measurement accuracy have been investigated and compared with PTW 60019 and IBA SFD reference dosimeters. Results: All of the 3D pixels had a linear and reproducible response to the dose rate. The sensitivity of a pixel decreases with its size, although even the smallest pixel has a high absorbed dose sensitivity (15 nC/Gy). The penumbra width measured with the smallest pixel size was consistent with the PTW microDiamond and differed by 0.2 mm from the IBA SFD diode. Conclusions: The study demonstrates that variation in pixel size do not affect the linearity of response with dose rate and the reproducibility of response. Due to the 3D geometry, the absorbed dose sensitivity of the detector remains high even for the smallest pixel, furthermore the pixel size was demonstrated to be of fundamental importance in the measurement of beam profiles. Highlights: Highly segmented pcCVD diamond detectors are fabricated using a pulsed laser grafitization technique. All size pixels have dose rate linearity, repeatability and response homogeneity. Small beam profile measurements with 3D detectors depend on the pixel size. Small pixel beam profiles are in good agreement with PTW microDiamond and IBA SFD silicon diode.